A cross-language study on citation practice in PhD theses - Soler Monreal, Carmen; Gil Salom, Luz (International Journal of English Studies, 2011)
Citation practice provides justification for arguments and allows a writer to indicate a rhetorical gap for her/his research and adopt a tone of authority. Claims must be supported with evidence, and writers must demonstrate an understanding of approaches and knowledge in their fields of specialisation, in order to persuade the examiners that the thesis is worthy of the award of a doctorate (Thompson, 2005b). Candidates need to keep the adequate interpersonal relationship with the immediate audience (the examiners). They have to evaluate the previous research in an area of study and to be respectful with previous claims from authorities in the disciplines. They also need to position themselves in relation to other disciplinary members and highlight their individual claims. This paper investigates contrastively how interactional resources of citation and, in particular reporting verbs, are deployed in the literature review chapters of PhD theses written in English and in Spanish.